Cultivation Technology of Melony Tree Seedling in Cups with Artificial Substrates - Kh. A. Adilov; N. Sh. Enileev; Sh. R. Usanov (Research Parks Publishers, 2021)
This scientific article reveals experimental materials on the use of artificial substrates and their volumetric ratios for growing papaya seedlings in plastic cups of various sizes from 392 cm3, 2649 cm 3 As a result of scientific research to identify the optimal sizes of cups filled with artificial substrates, a positive effect on the development of papaya seedlings was revealed when they are grown in plastic bags with diameter and height of 15 cm, filled with sand and humus in the ratio of artificial components (sand-humus, sawdust, rice husk)1:3.